Susceptibility of the cattle tick Boophilus microplus (Acari: Ixodidae) to isolates of the fungus Beauveria bassiana - Vieira Paião, J. D C [UNESP]; Monteiro, A. C. [UNESP]; Do Nascimento Kronka, S. [UNESP] (Springer Nature, 2001)
The susceptibility of the tick Boophilus microplus to Beauveria bassiana was evaluated by inoculating eggs, larvae and engorged females of the tick with five fungal isolates at concentrations of 106, 107 and 108 conidia/ml. Tick eggs (0.25 g) were immersed in 1 ml of a suspension of the different conidial concentrations for 1 min. Similar exposure was performed by immersion of 2000 larvae and homogeneous groups of nine engorged females in 2 and 20 ml of conidial suspension, respectively. Treated eggs, larvae and adults were placed in an incubator at 27 ± 1 °C and relative humidity above 80% for evaluation of the fungal action. All fungal isolates applied at all conidial concentrations reduced the hatching rate of larvae from treated eggs by 1.36-65.58% and increased the mortality rate of inoculated larvae by 0.8-70.49%. In the bioassay with engorged females, oviposition period was reduced by 9.69-47.80%, egg mass weight by 4.71-53.87%, estimated reproduction by 8.3-60.62%, egg production index by 5.03-54.20%, percent larval hatching by 0.27-13.96%, and the mortality rate of treated females was increased by 96.60-100%. The reduction of the estimated reproduction obtained for the treated groups ranged from 8.37 to 64.52%. The sporulation of the pathogen on dead females ranged from 3.70 to 88.88% depending on the isolate and concentration used. Isolates AM 09, CB 7 and JAB 07 were the most effective and effectiveness increased with increasing concentrations of conidia in the suspensions.
Keywords: Beauveria bassiana; Bioassay; Biological control; Boophilus microplus; Cattle tick entomopathogenic fungi; bioassay; colony forming unit; concentration (parameters); conidium; female; fungal infection; genetic susceptibility; hatching; humidity; incubation; microbiology; mortality; suspension cell culture; temperature; Acari; Bassiana; Beauveria; Bos taurus; Cordyceps bassiana; Fungi; Invertebrata; Ixodidae